Evaluation Of The Use Of SIMRS In Medical Record Using The PIC Method In The Simpang Lima Gumul Regional Hospital, Kediri - Eriskha Ayu Wardani; Mika Vernicia Humairo (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Hospital management information system or commonly called SIMRS is a form of application of information technology that serves to improve health service efforts in hospitals. The purpose of this study was to explore the evaluation of the use of SIMRS in the medical record section with the PIC method at SLG Kediri Hospital. The design of this study is a qualitative research with a phenomenological approach with the focus of the research directed at exploring the evaluation of the use of SIMRS in the medical record section with the PIC method at the SLG Kediri Hospital by triangulation. In addition, with a qualitative approach, it is hoped that the situation and problems encountered in these activities can be disclosed. The current performance of the hospital management information system is quite good, but the output produced is not in accordance with the wishes of the officers who use it. The information produced by the hospital management information system is not yet accurate and needs to be evaluated so that it has high accuracy and the resulting data is of high quality. In addition, there is a need for bridging so that the resulting data can be valid. The control aspect is quite good because there are data backups and authorization for SIMRS which not everyone can have an account to access. It is hoped that there will be confirmation in the form of regular monitoring for officers in completing patient data so that the information needed is appropriate and also the addition of computers so that services using SIMRS can be maximized and can minimize paper costs